Variations in Site Conditions and Blast Geometry on The Formation of Toxic Gas (Fumes) in Open-Pit Coal Mining - Maulana, Yuga; Purwiyono, Taat Tri; Tuheteru, Edy Jamal; Marmer, Handoyo; Hartami, Pantjanita Novi (Graduate School of Universitas Syiah Kuala, 2024)
The blasting activity generates one of the effects in the form of toxic gases (fumes) that can disturb living beings around them. Fumes formation is formed by the reaction of the explosive material not in a zero oxygen balance condition, and is influenced by several factors including the condition of the blast hole, rock moisture content, blast hole temperature and relative humidity, sleep blast, explosive material ratio, and poor confinement stemming. This study investigates the variations in site condition and blast geometry on the formation fumes in open-pit coal mining. This research was conducted at the coal mine of Kaltim Prima Coal (PT KPC) to quantitatively measure the levels of toxic gas (fumes) resulting from blasting activities. In-situ measurements were conducted using a gas detector suspended above a drone. From the measurement results, it was found that blasting activities at the PT KPC coal mine produce CO and NO2 gases in toxic gas visual conditions at Levels 0 and 1A. The CO gas levels resulting from blasting activities ranged from 60.34 to 324.79 ppm, and the NO2 gas levels ranged from 0.3 to 2.11 ppm. From the trial results, by altering the explosive material ratio, toxic gas visual conditions were observed at Level 2A with CO gas levels of 360.29 ppm and NO2 gas levels of 3.16 ppm. The formation of CO and NO2 gases from blasting is influenced by the blast hole temperature and humidity, as well as differences in explosive material ratios. Based on the gas CO and NO2 level measurements, according to the threshold values with the maximum exposure level for humans over a 15-minute period for both gases, it was determined that workers could safely return to the blasting site in less than 1 minute.